Spatial and Temporal Variability in Rainfall Erosivity Under Alpine Climate: A Slovenian Case Study Using Optical Disdrometer Data - Bezak, Nejc; Petan, Sašo; Mikoš, Matjaž (Frontiers in Environmental Science, 2021)
Rainfall erosivity is one of the most important parameters that influence soil erosion rates. It is characterized by a large spatial and temporal variability. For example, in Slovenia, which covers around 20,000 km2, the annual rainfall erosivity ranges from less than 1,000 MJ mm ha-1 h-1 to more than 10,000 MJ mm ha-1 h-1. Drop size distribution (DSD) data are needed to investigate rainfall erosivity characteristics. More than two years of DSD measurements using optical disdrometers located at six stations in Slovenia were used to investigate the spatial and temporal variability in rainfall erosivity in Slovenia. Experimental results have indicated that elevation is a poor predictor of rainfall erosivity and that erosivity is more strongly correlated to the mean annual precipitation. Approximately 90% of the total kinetic energy (KE) was accounted for in about 35% of 1-minute disdrometer data. The highest 1-minute intensities (I) and consequently also kinetic energy values were measured in summer followed by autumn and spring. The local KE-I equation yielded an acceptable fit to the measured data in case of all six stations. The relatively large percentage of 1-minute rainfall intensities above 5 mm/h can at least partially explain some very high annual rainfall erosivity values (i.e. near or above 10,000 MJ mm ha-1 h-1). Convective and large-scale precipitation events also result in various rainfall erosivity chracteristics. The station micro-location and wind impacts in case of some stations yielded relatively large differences between the data measured using the optical disdrometer and the pluviograph. Preliminary conclusions have been gathered, but further measurements are needed to get even better insight into spatial and temporal variability in rainfall erosivity under Alpine climate in Slovenia.